Enhancement on migration and biodegradation of Diaphorobacter sp. LW2 mediated by Pythium ultimum in soil with different particle sizes - Li, Jialu; Hong, Mei; Lv, Jing; Tang, Rui; Wang, Ruofan; Yang, Yadong; Liu, Na (Frontiers in Microbiology, 2024)
The composition and structure of natural soil are very complex, leading to the difficult contact between hydrophobic organic compounds and degrading-bacteria in contaminated soil, making pollutants hard to be removed from the soil. Several researches have reported the bacterial migration in unsaturated soil mediated by fungal hyphae, but bacterial movement in soil of different particle sizes or in heterogeneous soil was unclear. The remediation of contaminated soil enhanced by hyphae still needs further research. In this case, the migration and biodegradation of Diaphorobacter sp. LW2 in soil was investigated in presence of Pythium ultimum. Hyphae could promote the growth and migration of LW2 in culture medium. It was also confirmed that LW2 was able to migrate in the growth direction and against the growth direction along hyphae. Mediated by hyphae, motile strain LW2 translocated over 3 cm in soil with different particle size (CS1, 1.0-2.0 mm; CS2, 0.5-1.0mm; MS, 0.25-0.5 mm and FS, ＜0.25 mm), and it need shorter time in bigger particle soils. In inhomogeneous soil, hyphae participated in the distribution of introduced bacteria, and the total number of bacteria increased. Pythium ultimum enhanced the migration and survival of LW2 in soil, improving the bioremediation of polluted soil. The results of this study indicate that the mobilization of degrading bacteria mediated by Pythium ultimum in soil has great potential for application in bioremediation of contaminated soil.